The CeHRes Roadmap 2.0: Update of a Holistic Framework for Development, Implementation, and Evaluation of eHealth Technologies - Hanneke Kip; Nienke Beerlage-de Jong; Lisette J E W C van Gemert-Pijnen; Saskia M Kelders (Journal of Medical Internet Research)
To ensure that an eHealth technology fits with its intended users, other stakeholders, and the context within which it will be used, thorough development, implementation, and evaluation processes are necessary. The CeHRes (Centre for eHealth and Wellbeing Research) Roadmap is a framework that can help shape these processes. While it has been successfully used in research and practice, new developments and insights have arisen since the Roadmap’s first publication in 2011, not only within the domain of eHealth but also within the different disciplines in which the Roadmap is grounded. Because of these new developments and insights, a revision of the Roadmap was imperative. This paper aims to present the updated pillars and phases of the CeHRes Roadmap 2.0. The Roadmap was updated based on four types of sources: (1) experiences with its application in research; (2) literature reviews on eHealth development, implementation, and evaluation; (3) discussions with eHealth researchers; and (4) new insights and updates from relevant frameworks and theories. The updated pillars state that eHealth development, implementation, and evaluation (1) are ongoing and intertwined processes; (2) have a holistic approach in which context, people, and technology are intertwined; (3) consist of continuous evaluation cycles; (4) require active stakeholder involvement from the start; and (5) are based on interdisciplinary collaboration. The CeHRes Roadmap 2.0 consists of 5 interrelated phases, of which the first is the contextual inquiry, in which an overview of the involved stakeholders, the current situation, and points of improvement is created. The findings from the contextual inquiry are specified in the value specification, in which the foundation for the to-be-developed eHealth technology is created by formulating values and requirements, preliminarily selecting behavior change techniques and persuasive features, and initiating a business model. In the Design phase, the requirements are translated into several lo-fi and hi-fi prototypes that are iteratively tested with end users and other stakeholders. A version of the technology is rolled out in the Operationalization phase, using the business model and an implementation plan. In the Summative Evaluation phase, the impact, uptake, and working mechanisms are evaluated using a multimethod approach. All phases are interrelated by continuous formative evaluation cycles that ensure coherence between outcomes of phases and alignment with stakeholder needs. While the CeHRes Roadmap 2.0 consists of the same phases as the first version, the objectives and pillars have been updated and adapted, reflecting the increased emphasis on behavior change, implementation, and evaluation as a process. There is a need for more empirical studies that apply and reflect on the CeHRes Roadmap 2.0 to provide points of improvement because just as with any eHealth technology, the Roadmap has to be constantly improved based on the input of its users.